META- ANALYSIS OF THE USE MOVIE TRAILER IN EFL CLASSROOM - Saidah, Umi Halimatus; Islam, Aang Fatihul (STKIP PGRI Jombang, 2017)
The scenes in the trailer shown are all sorts of interesting and prominent scenesto attract the attention of potential viewers and be able to describe the entire contents of the movie without giving too much information. The trailer was created to promote theatrical release of the movie and the movie trailer was a clip containing all the parts of the advertised movie, shown before other movie screenings in the cinema, and aimed for the audience to come to watch. The best way to teach English is to use interesting material, appropriate teaching methods, the use of technology that can be one of the important and effective support tools. Meta-analysis is essentially a synthesis of a topic taken from several research reports. Based on the synthesis is drawn conclusions about the topic under study. This research uses some similar research results as basic data in conducting studies and conclusions. From the same five studies, it is concluded that Movie Trailer is effective as a learning medium because it can improve understanding in English learning.